STUDY OF HIGHER EDUCATION STUDENTS’ PERCEPTIONS ON CRITICAL THINKING PHENOMENON - HABRUSIEVA, Nataliia; SHOSTAKIVSKA, Nadia (Physical and Mathematical Education, 2024)
The article presents the results of the correspondence ideas analysis about the critical thinking phenomenon among the students of Ternopil Ivan Puluj National Technical University (Ukraine) we interviewed with theoretical developments, in particular, the classification of critical thinking skills identified by the American Philosophical Association (interpretation, analysis, evaluation, conclusion, explanation, and self-regulation) and the components of critical thinking identified by Ukrainian scientist V. Nadurak (normative, discretionary and prescriptive components). Formulation of the problem. The formation of students’ critical thinking is a complex and multidirectional process, defined in the national Higher Education Standards as one of the main tasks of professional training for a competent specialist. Its implementation in pedagogical practice requires a clear understanding of the essence and content of the concept of "critical thinking," its structure and components, and considering the specifics of a particular educational environment, objective conditions, and circumstances in which the educational process occurs. However, many theoretical scientific approaches to interpreting critical thinking nature make it difficult for teachers and students to define and understand it. Materials and methods: theoretical (a systematic analysis method of theoretical scientific approaches and concepts presented in the works of Ukrainian and foreign scientists, which explain the phenomenon of critical thinking), empirical (surveys, questionnaires), and statistical data processing methods (we used Power BI Desktop for content analysis, Microsoft Excel, and IBM® SPSS® Statistics for statistical analysis). Results. The study’s results revealed peculiarities in the respondents’ (TNTU, Ukraine) understanding of the critical thinking nature, including the definition of critical thinking as the ability to act quickly in extreme crises and a high percentage of distrust of the opinions of others and the media. This specificity is primarily due to the stressful situations in which students have lived since the beginning of russia’s military aggression against Ukraine. There needs to be more formation of the ability to cognitive explanation and self-regulation of respondents, namely skills necessary for the formation of critical thinking is recorded. Conclusions. The article clarifies the meaning of the concept of "critical thinking" considering the peculiarities of its interpretation by students of TNTU, Ukraine. Ways to activate critical thinking skills in the educational process are outlined. They argue for the need to pay attention to the emotional well-being of students during the war and the use of methods and forms of education in the educational process aimed at increasing stress resistance and resilience.